Effectiveness of Role Playing and Demonstration to Improve Smash the Tennis Technique (Department of Physical Education, Sport, Health and Recreation, 2020)
This study aims to examine and analyze the effectiveness of the use of learning methods, namely role playing and demonstration in improving tennis smash technique. This type of research itself is comparative, with matched subject design, involving 24 samples. The instrument used was a back-board test, analyzed using tests: normal, homogeneity, and hypothesis with a significance level of 0.005. The results obtained from this study include: (1) There is no significant effect between role playing on the smash technique; (2) There is an influence between demonstration on the smash technique; and (3) demonstration method is better than role playing on the tennis smash technique. This research provides benefits for the development of tennis in Papua, coaches and tennis athletes need new methods of training. Should an amateur student or athlete who is just learning tennis try the results of this research method and not be discouraged quickly in training.